Adsorption mode of neurotensin family peptides onto a colloidal silver surface: SERS studies. (21st November 2012) - Proniewicz, Edyta; Ozaki, Yukihiro; Kim, Younkyoo; Proniewicz, Leonard M.
<x xml:space="preserve">Abstract</x> Kinetensin (KN) and its amino acids 1–8 fragment ([des‐Leu9]KN), neuromedin N (NMN), and xenopsin (XP) and its two analogs (human XP‐1/xenin‐8 and XP‐2) belong to the neurotensin family of peptides and are known to stimulate the growth of human tumors. In this work, we report surface‐enhanced Raman scattering (SERS) studies of these peptides and discuss their structures, orientation, and mode of adsorption onto a colloidal assembly of apparently randomly adhering Ag spheres with diameters of approximately 20 – 25 nm. We show that small alternations in both the amino acid composition and tertiary structure, which induce striking biological in vitro, were responsible for the observed spectroscopic changes. Copyright © 2012 John Wiley & Sons, Ltd.